Kepastian Hukum Terhadap Surat Girik Sebagai Dasar Bukti Pendaftaran Hak Atas Tanah - H. Masnadi; Ahmad Muliadi; Irawan Santosa (Jurnal Nuansa Kenotariatan, 2019)
Research carried out on land rights registration certificate with evidence girik, where the book letter C in the Village, which refers to Law No. 5 of 1960 on Agrarian Principles, Government Regulation No. 24 Year 1997 on Land Registration Board Decree National Land and Circular Head of the National Land Agency. Specification used in the normative analysis. Research stage through literature and interviews. The method of data analysis conducted qualitative normative.Based on the results of research and analysis of the rules and regulations, that the letter Girik have a certificate of registration of legal certainty for Land Rights through the assertion of rights / acknowledgment of rights, although there is no letter C in wards book.